Taxation of Rent from Ricardo to George - Başak Atan (Maliye Çalışmaları Dergisi)
Due to current urbanism practices that are rent-oriented and far from being sustainable, the need to purify cities from the pressure of rent has arisen. This need has prompted professionals to seek solutions. The land value taxation method which can be defined as the suggestion of taxing the land in full or at a higher rate compared to the improvement on it, unlike the classical property tax approach, is a tool that needs to be worked on with the potential of providing the transfer of urban rent to the publicby appropriating rent through taxation. This tool can also be used to solve various rent-based urban problems. In this study, which examines land value taxation in terms of the history of economic thought, the development of the land value taxation proposal is summarized by explaining the position of Ricardo’s rent theory in the aforesaid development and the approaches of two thinkers regarding the rent and taxation of rent are compared. The structure of the study is principally based on two books: Henry George’s “Progress and Poverty” and David Ricardo’s “Principles of Political Economy and Taxation”. As a result of the analysis made in this study, it can be said that Ricardo and George hold differing views of rent which are both based on different foundations. In relation to this, it has been deduced that Henry George, while questioning the system of private ownership in land while researching the paradox of progress and poverty, and proposing land value tax for returning rent to the public that created the progress, is more effective in finding solutions to the problem of returning the rent to the public.